Leadership Relationship of The Head of Nursing with The Motivation of The Work of Implementing Nurses in North Sumatra Lung Special Hospital in 2021 - Asnija Sinambela; Zulfendri Zulfendri; R Kintoko Rochadi (Science Midwifery, 2021)
Leadership is the ability to give constructive influence to others to make a cooperative effort to achieve a planned goal. Motivation is something that is strength, energy, or power, or a complex situation and preparedness is an impulse in an individual to move towards a specific goal. A nurse's motivation can also experience changes caused by factors that affect her. The purpose of this study was to analyze the relationship between the leadership of the head of nursing to the motivation of the work of the implementing nurse at the North Sumatra Lung Special Hospital. This research is an analytical survey research using the cross-sectional method. The population in this study was 53 nurses. The sampling technique used is the total population. Data analysis using univariate, bivariate analysis with Chi-Square test of Chi-Square person value to multivariate. Statistic test results with analysis there is a relationship between the leadership of a nursing head based on the soft skills of respondents ρ = 0.012 and hard skills respondents with a value of ρ = 0.004 (ρ value < 0.05) with the motivation of the work of the implementing nurse at the Lung Special Hospital North Sumatra. The test results concluded there was a significant relationship between the leadership of the head of nursing and the motivation of the work of the implementing nurse at the North Sumatra Lung Special Hospital. It is recommended to further increase the motivation of workers in order to achieve the vision and mission of the hospital and increase the sense of responsibility of nurses to the tasks carried out.